The Application of Servqual and IPA Methods to Identify Areas for Improvement in Services at Mangggarai Station - Saputri, Wandha Indah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This study aims to assess and improve the quality of service on the Jabodetabek KRL at Manggarai Station which has experienced an increase in the number of passengers and density, especially during peak hours. This increase causes several challenges, including inconvenience for passengers. The SERVQUAL and Important Performance Analysis (IPA) methods were used to identify and address gaps between expectations and passengers' perceptions of the services provided by the station. The study involved the distribution of questionnaires designed to measure five dimensions of service quality including reliability, responsiveness, assurance, empathy, and physical evidence. The results of the analysis proved the existence of several significant gaps that require immediate corrective action. Based on these findings, strategic recommendations were developed for PT Kereta Commuter Indonesia in order to optimize operations and improve customer satisfaction. This research provides new insights into the existing literature by highlighting the importance of service quality management in the public transportation sector, particularly on the KRL Commuter Line.